Hubungan Kejadian Stunting Dengan Capaian Perkembangan Anak di wilayah Kerja Puskesmas Motolohu Kabupaten Pohuwato - Siti Nur Annisa Punuh; Andi Akifa Sudirman; Dewi Modjo (Institut Nalanda, 2023)
Stunting is a chronic malnutrition problem caused by a lack of nutrition for a long time, resulting in growth disorders in children, namely the child's height is lower or shorter (dwarf) than the standard age. Stunting can cause cognitive or intelligence, motor, and verbal development to not develop optimally, increasing the risk of obesity and other degenerative diseases. The design of research used an analytic survey method with a cross-sectional approach. The population were all stunted children aged 24-60 months with a total of 33 people. The sample consisted of 33 stunted children aged 24-60 months in the working area of the Motolohu Health Center, Pohuwato Regency, using a total sampling technique. The instruments used questionnaires and microtoise measuring devices. Statistical test using chi-square test. The results showed that 6 children (18.2%) were stunted in the short category, with 2 children with appropriate development, 4 children with doubt, 0 children with deviations. Meanwhile, there were 27 children (81.8%) with stunting in the very short category, 0 children showed appropriate development, 20 children doubted, 7 children had deviations. The conclusion, there is a relationship between the incidence of stunting and child growth achievements in the working area of the Motolohu Health Center, Pohuwato Regency, with a value of p = 0.005 with a <0.05.